1986
DOI: 10.1002/bit.260280125
|View full text |Cite
|
Sign up to set email alerts
|

Phenanthrene degradation by Beijerinckia sp. B8/36

Abstract: The use of fossil fuels has greatly increased the ubiquity of polynuclear aromatic hydrocarbons (PAHs) in the environment, and their potential toxicity has generated considerable interest in the ability of microorganisms to utilize and/or detoxify these pollutants.One PAH of concern is phenanthrene. Numerous microbial species are known to degrade phenanthrene and there appear to be several metabolic routes available, depending upon the species, strain, and even the cultural conditions.',' Although there is a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 2 publications
2
8
0
Order By: Relevance
“…The isolated strain was further characterized for the effect of environmental factors such as pH and temperature. In agreement with Strandberg et al (1986) and Weissenfels et al (1990), who studied the influence of pH and temperature on PAH degradation by pure bacterial cultures, pH 7.0 and 30°C were determined to be optimal for microbial growth and pyrene degradation.…”
Section: Discussionsupporting
confidence: 56%
“…The isolated strain was further characterized for the effect of environmental factors such as pH and temperature. In agreement with Strandberg et al (1986) and Weissenfels et al (1990), who studied the influence of pH and temperature on PAH degradation by pure bacterial cultures, pH 7.0 and 30°C were determined to be optimal for microbial growth and pyrene degradation.…”
Section: Discussionsupporting
confidence: 56%
“…Environmental factors such as temperature have a greater influence on degradation of xenobiotics in soil and water (Sherill and Saylor 1980;Strandberg et al 1986). The results obtained by examining the influence of temperature on growth and degradation were supported by the observations of Weissenfels et al (1990), who also reported a decrease in growth of P. paucimobilis at 30°C, while phenanthrene degradation increased up to a temperature of 35 ° C.…”
Section: Discussionmentioning
confidence: 99%
“…Phenanthrene, which is composed of three fused benzene rings, is a relatively soluble PAH (Dzombak 1984) that can be degraded by m a n y microorganisms (Bumpus 1989;Ghosh and Mishra 1983;Guerin and Jones 1988a, b;Strandberg et al 1986). This paper deals with the characterization of phenanthrene degradation under different conditions by a pure bacterial culture isolated from a contaminated soil surrounding a former coking plant.…”
Section: Introductionmentioning
confidence: 99%
“…Naphthalene, salicylate and isopropyl-(-D-thiogalactopyranoside (IPTG) were added to the basal medium either alone or in combination, so as to induce the plasmidencoded genes. In case of the media supplemented with naphthalene, the MSM was prepared in naphthalene-saturated distilled water (Strandberg et al 1986). Salicylate and IPTG were added to the media at a ®nal concentration of 2 mmol l À1 and 1 mmol l À1 , respectively, for induction purposes.…”
Section: Bacteria Media and Culture Conditionsmentioning
confidence: 99%